ASSESSING THE IMPACT OF OCCLUSAL RELIEF IN ENDODONTIC THERAPY ON POSTOPERATIVE PAIN PATTERNS IN PATIENTS AFFLICTED WITH IRREVERSIBLE PULPITIS AND APICAL PERIODONTITIS. - Mohammed Dhaher Alshammari1, Zidan Muead Alanazi2, Khalid Mohammed Aldhafeeri3, Abdulmajeed Faris Alanezi4, Jamal Hameed Alshammari5, Talal Mohammed Aldhafeeri6, Fatemah Draia Alrasheedi7, (Chelonian Research Foundation, 2022)
Background and Aim: Nonsteroidal anti-inflammatory medications are widely used to treat postoperative pain. Corticosteroids, long-acting anesthesia, and occlusal relief are among of the therapy techniques utilised to relieve inter or postoperative pain. The goal of this research was to see the impact of occlusal relief affected the considerable pattern towards postoperative pain at different time intervals in patients having apical periodontitis and irreversible pulpitis. Material and Methods: This research used a prospective study among individuals were underwent RCT in teeth concerning necrotic pulp, vital pulp, or vital pulp that undergone treatment and treated for major symptomatic irreversible pulpitis by one endodontic clinician over a one-year period, or individuals undergone root canal retreatment. Sixty posterior teeth along with irreversible pulpitis and minor tenderness towards percussion were substantially included in this randomised trial. The root canal procedure was started, and biomechanical preparation was completed. After applying calcium hydroxide as an intracanal medicament, a closed dressing was applied. The selected patients have been randomly allocated to one of two groups: the experimental group having occlusal contacts were alleviated (n = 50) and the other control group included occlusal contacts were left intact (n = 50). The “Heft Parker Visual Analogue Scale” was used to record and analyse postoperative pain at various intervals. Results: Overall, a total of 100 patients were treated, with 50 in each group. Each group had 50 patients evaluated. There were 64 (64%) women and 36 (36%) men among the 100 patients. The discomfort felt by the patients dramatically decreased over time and was constant in both groups at the 6-hour follow-up. At 6 h, there is no statistically significant change in pain status among the control and experimental groups (P > 0.05). Conclusion: In conclusion, the study stated there was no statistically significant difference in postoperative discomfort incidence between groups. In the occlusion eased group, the significant pattern of postoperative pain did indicate a steady reduction. There were flare-ups in the occlusion intact group. This shows that occlusal reduction could be useful in preventing flare-ups during endodontic treatment. Key Words: Endodontic treatment, Root canal treatment, Occlusal relief, Postoperative pain